Wtórna cukrzyca jako rzadkie powikłanie choroby spichrzeniowej glikogenu 1a: opis przypadku i przegląd literatury - Aggarwal, Anshita; Patel, Deepika; Kulshreshtha, Bindu (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Glycogen storage diseases (GSDs) are disorders of carbohydrate metabolism and hypoglycemia is their hallmark. Secondary diabetes with glycogen storage disease, which seems rather paradoxical, has been rarely reported. A 13-year-old girl previously diagnosed to have GSD 1a presented to the emergency with multiple episodes of vomiting and loss of consciousness. She had hyperglycemia, ketonuria, hyperlactatemia and metabolic acidosis, suggestive of diabetic ketosis with acidosis possibly contributed by both high serum lactate and serum ketones. Her glycated hemoglobin was high, with detectable serum insulin levels, which suggested secondary diabetes in the background of GSD Ia. Her management posed a therapeutic challenge. She was managed with insulin and achieved good glycemic control. We wish to conclude that GSD may rarely lead to secondary diabetes as a complication and the management is complex owing to the nature of the disease. Insulin remains the mainstay of the treatment.